Development of a gene reporter system in moderately halophilic bacteria by employing the ice nucleation gene of Pseudomonas syringae. - Arvanitis, N (1995)
The expression of the ice nucleation gene inaZ of Pseudomonas syringae in several moderate halophiles was investigated to establish its utility as a reporter for promoter activity and gene expression studies in these biotechnologically and environmentally important bacteria. A promoterless version of inaZ was introduced in two different restriction sites and at both orientations in a recombinant plasmid able to replicate in moderate halophiles and, in particular, within the sequence of its pHE1 part, a native plasmid of Halomonas elongata. One orientation of both recombinant constructs expressed high levels of ice nucleation activity in H. elongata and Volcaniella eurihalina cells, indicating that inaZ was probably introduced in the correct orientation downstream of putative native promoters. A recombinant construct carrying a tandem duplication of inaZ at the same orientation gave significantly higher ice nucleation activity, showing that inaZ is appropriate for gene dosage studies. The ice nucleation gene was also expressed in H. elongata and V. eurihalina under the control of Pbla (the promoter of the beta-lactamase gene of Escherichia coli) and Ppdc (the promoter of the pyruvate decarboxylase gene of Zymomonas mobilis). One of the inaZ reporter plasmids expressing high levels of ice nucleation activity under the control of a native putative promoter was also transferred in Halomonas subglaciescola, Halomonas meridiana, Halomonas halodurans, and Deleya halophila. In all cases, Ice+ transconjugants were successfully isolated, demonstrating that inaZ is expressed in a wide spectrum of moderately halophilic species.